2019
DOI: 10.1371/journal.pone.0215578
|View full text |Cite
|
Sign up to set email alerts
|

Manuring practices in the first millennium AD in southern Sweden inferred from isotopic analysis of crop remains

Abstract: This study uses crop stable nitrogen isotope analysis of charred grain to explore manuring practices in arable production at the affluent regional center Uppåkra and a set of smaller surrounding sites, dating to the first millennium AD in southern Sweden. The isotopic analysis focuses on hulled barley, the principle crop in the Scandinavian Iron Age, and the minor crops: bread wheat, emmer wheat, rye and oat, are included to compare manuring practices in cultivation of other crop species during this period. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…A recently published compilation and modeling of pollen data shows that the fertile soils of southwestern Scania during the Iron Age were characterized by a very open, almost treeless landscape, and that arable land covered c. 20-35% of the land area (Lagerås and Fredh 2019). Another recent study determined nitrogen isotope values of archaeological cereal grains recovered from Uppåkra and six nearby sites (Larsson, Bergman, and Lagerås 2019). Larsson, Bergman, and Lagerås (2019) found that the grains had high nitrogen isotope values and attributed these to systematic addition of manure to arable fields during most of the first millennium AD.…”
Section: Implications For Long-distance Movement Of Livestock and Grainmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published compilation and modeling of pollen data shows that the fertile soils of southwestern Scania during the Iron Age were characterized by a very open, almost treeless landscape, and that arable land covered c. 20-35% of the land area (Lagerås and Fredh 2019). Another recent study determined nitrogen isotope values of archaeological cereal grains recovered from Uppåkra and six nearby sites (Larsson, Bergman, and Lagerås 2019). Larsson, Bergman, and Lagerås (2019) found that the grains had high nitrogen isotope values and attributed these to systematic addition of manure to arable fields during most of the first millennium AD.…”
Section: Implications For Long-distance Movement Of Livestock and Grainmentioning
confidence: 99%
“…Another recent study determined nitrogen isotope values of archaeological cereal grains recovered from Uppåkra and six nearby sites (Larsson, Bergman, and Lagerås 2019). Larsson, Bergman, and Lagerås (2019) found that the grains had high nitrogen isotope values and attributed these to systematic addition of manure to arable fields during most of the first millennium AD. These studies both point to intensive crop production in the area, and for that reason, it seems unlikely that farmers in the investigated area had the need to import large quantities of grain from regions outside.…”
Section: Implications For Long-distance Movement Of Livestock and Grainmentioning
confidence: 99%
“…There was evidence to indicate the latter, but excavation uncovered additional dome-shaped clay ovens. Analyses of charred grains found at one of the ovens show that it was used to dry the mash for brewing beer (M. Larsson et al 2018;2019b). This suggests the allocation of a part of the settlement area for making beer over several centuries.…”
Section: The Evidence Of Economic Activities and Craftsmentioning
confidence: 99%
“…By comparison with other samples in Uppåkra, these are of a somewhat larger dimension, refl ecting sorted grains from crop-processing activities. The long-term trend of crop cultivation on manured soils, evidenced from high δ 15 N values in grain, signals agricultural wealth in the area and this pairs with the economic affl uence that is ascribed to the regional center Uppåkra (M. Larsson et al 2019b). Flax and gold of pleasure were grown, mainly for oil production.…”
Section: Botanical Materialsmentioning
confidence: 99%
“…Within the terrestrial ecosystem, it can distinguish C 3 from C 4 plant sources; on the other hand, the nitrogen isotopic signature (δ 15 N) is useful for determining the trophic level of the analyzed individual(s) [ 1 , 2 , 18 , 19 ]. It would be worth analyzing coeval plant and animal specimens along with human samples in order to better interpret the ecological context and to evaluate possible variations of the isotopic values due to specific agriculture and breeding practices, and/or to the analyzed sites’ geographical location and ecology [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%